SAT0633-HPR Articular Involvement of the Scleroderma Hand: An Assessment Protocol for Planning Occupational Therapy Strategies. (9th June 2015) - Mercanti, C.; Zingarello, L.A.; Franchi, F.; Sartini, S.; Giuggioli, D.; Ferri, C.; Mascia, M.T.
Abstract : Background: Systemic sclerosis (SSc) is a rare inflammatory connective tissue disease acquired, chronic, progressive of unknown etiology characterized by irregular autoimmune response, changes in the small circle due to vascular disease, fibrosis of the skin and internal organs. Hand impairment is a major cause of morbidity and disability in about 90% of SSc patients Although physiotherapy and rehabilitation programs to prevent and reduce the disability resulting from osteo-articular and skin involvement are recommended, only a few studies have been published on this feature. Objectives: Our study aims an analysis of scleroderma hand through the application of instrumental tests and rating scales to suggest a specific evaluation protocol in order to highlight the main anomalies for planning occupational therapy strategies and to have specific outcome measure. Methods: The study was conducted on 45 patients with SSc. In the protocol were included total active motion-TAM (Strickland), strength of the grip (Jamar dynamometer and pinchmeter) and the evaluation of 16 different types of prehension of objects encountered during activities of daily life. Results: The Strickland measurement showed a symmetrical involvement of the hands for almost all patients (93%); furthermore observed that only 30% of patients have an excellent level in TAM (percentage of scoring higher 85%). A statistically significant reduced total active movement of the dominant hand was documented in diffuse SSc. Furthermore, the fingers more limited and therefore with lower TAM are the 2nd and 5th finger in both hands. At the second finger there is a statistically significant weaker strength of dominant hand related to disease duration in patients with dSSc (P value equals 0.0021). The grip strength (Jamar Dynamometer and Jamar pinchmeter) is extremely reduced in 75% of patients and focuses mainly on the dominant hand. If <15 kg (below normal range), the difference between the strength of dominant and non dominant hand is considered to be very statistically significant and the dominant is weaker (P value <0.017); in subjects without involvement of the hands with strength normal, dominant hand is stronger but there are not statistical difference (p=0.55) The evaluation of 16 different types of prehension tested by a set of objects of different shapes has documented the impairment mainly of palmar grip (44%), tip to tip (37%) and vice (30%), followed by thenar grip, spherical grip and three jaw in a few cases. Conclusions: The documentation for greater involvement of the dominant hand with a reduction of the ROM in particular of 2 and 5 finger associated to decreased grip strength focus on confirm the importance of the hand use in daily life as the cause of greater disease damage. It is essential to plan quickly in patients with early systemic sclerosis an educational program to make the best use of work strategies equally distributed between dominant and non dominant hand and replacement activities for digit handheld, end-to- terminal and vice grip. Disclosure of Interest: None declared